2018
DOI: 10.1016/j.ajog.2017.12.206
|View full text |Cite
|
Sign up to set email alerts
|

The past, present, and future of selective progesterone receptor modulators in the management of uterine fibroids

Abstract: Uterine fibroids are common in women of reproductive age and can have a significant impact on quality of life and fertility. Although a number of international obstetrics/gynecology societies have issued evidence-based clinical practice guidelines for the management of symptomatic uterine fibroids, many of these guidelines do not yet reflect the most recent clinical evidence and approved indication for one of the key medical management options: the selective progesterone receptor modulator class. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 51 publications
0
30
0
1
Order By: Relevance
“…After summarizing the evidence on ulipristal acetate (UPA) they proposed an algorithm in which UPA plays an important role as medical pretreatment for hysteroscopic and laparoscopic fibroid surgery and for intermittent long-term use to prevent surgery. 1 However, in our opinion the currently available evidence does not support the implementation of this policy in daily practice (yet).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…After summarizing the evidence on ulipristal acetate (UPA) they proposed an algorithm in which UPA plays an important role as medical pretreatment for hysteroscopic and laparoscopic fibroid surgery and for intermittent long-term use to prevent surgery. 1 However, in our opinion the currently available evidence does not support the implementation of this policy in daily practice (yet).…”
mentioning
confidence: 81%
“…This is an inherently different population from other studies that have previously identified risk factors for cesarean and include women who may start labor with a favorable cervix and/or women who present in labor. [1][2][3][4] The examples that Dr San Roman provided are looking at overall risk of cesarean in a pregnancy, not specifically focusing on women undergoing an induction with an unfavorable cervix. While they are interesting tools, they do not address the same question nor the same population studied in our article.…”
mentioning
confidence: 99%
“…The choice of which drug should be eventually prescribed before surgery should take into account the characteristic of myomas (size, number, and location), efficacy of treatment, incidence and severity of AEs, route of administration, preference of patients and surgeons [34]. Anyway, all these preoperative medical options share some potential drawbacks such as cost, delay in the surgical procedure, additional consultations, and drug-related AEs.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to thank Dr Middelkoop and Dr Huirne for their comments related to our recent publication. 1 Their letter raises several issues that we would like to address.…”
Section: Replymentioning
confidence: 99%